PENGARUH ATMOSFER TOKO DAN DAYA TARIK PROMOSI PENJUALAN TERHADAP KEPUASAN PELANGGAN DAN NIAT BELI ULANG (DI MATAHARI MALL BALI GALERIA KUTA) - Kartika Yudha, I Putu Gede Manik; Suprapti, Ni Wayan Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.07.TAHUN 2018, 2018)
This study aims to determine the influence of store atmosphere and sales promotion appeal to customer satisfaction and re-purchase intention (in Matahari Mall Bali Galeria Kuta). The population in this study is all customers who have made purchases at least three times (3x) at Matahari Department Store Mall Bali Galeria. Respondents as many as 125 customers are visitors of Matahari Mall Bali Galeria taken by using purposive sampling. The data were analyzed by descriptive statistic in the mean of count and inferential statistic namely Partial Least Squares (PLS). The result of the research shows that (1) store atmosphere has positive and significant effect to customer satisfaction, (2) store atmosphere has positive and significant effect to repurchase intention, (3) sales promotion appeal positively and significantly to customer satisfaction, (4) the pull of sales promotion has a positive and significant impact on repurchase intention, and (5) customer satisfaction has a positive and significant impact on repurchase intention.